2012
DOI: 10.1111/j.1532-7078.2012.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of Early Prosocial Behavior: Parents’ Talk About Emotions is Associated With Sharing and Helping in Toddlers

Abstract: What role does socialization play in the origins of prosocial behavior? We examined one potential socialization mechanism, parents’ discourse about others’ emotions with very young children in whom prosocial behavior is still nascent. Two studies are reported, one of sharing in 18- and 24-month-olds (n = 29), and one of instrumental and empathy-based helping in 18- and 30-month-olds (n = 62). In both studies, parents read age-appropriate picture books to their children and the content and structure of their em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
193
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(210 citation statements)
references
References 79 publications
8
193
1
8
Order By: Relevance
“…This study provides some evidence that instrumental helping and emotional helping do not develop in parallel, and is in line with the view that partly different mechanisms might subserve these early forms of prosocial action. Moreover, in a recent study Brownell et al (2012) showed that the quality of parents' talk about emotions had an impact on children's empathic responding and sharing, but not on their instrumental helping behavior. Finally, Eisenberg et al (1999) conducted a longitudinal study to examine consistency in the development of prosocial behavior from the preschool years to adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…This study provides some evidence that instrumental helping and emotional helping do not develop in parallel, and is in line with the view that partly different mechanisms might subserve these early forms of prosocial action. Moreover, in a recent study Brownell et al (2012) showed that the quality of parents' talk about emotions had an impact on children's empathic responding and sharing, but not on their instrumental helping behavior. Finally, Eisenberg et al (1999) conducted a longitudinal study to examine consistency in the development of prosocial behavior from the preschool years to adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…Emotion understanding, given its robust associations with EMST, is one logical pathway (de Rosnay and Hughes, 2006; Thompson, 2006). Greater emotion understanding promoted by frequent parental EMST may help children infer the other's need and generate an appropriate prosocial response in a complex, affectively charged situation (Denham et al, 2007; Ensor et al, 2011; Brownell et al, 2013). Emotion and mental state discourse may also operate on children's prosocial motivations by facilitating empathy inductions, leading to internalized moral dispositions that underlie prosocial behavior toward those in distress (Hoffman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One set of studies found that emotion talk, particularly the elicitation of emotion words [12], was correlated with behavioral assessments of young children's sharing and emotion-based helping, but not with instrumental helping [13]. Further research focused on specific social-cognitive skills and social experiences.…”
Section: Antecedents and Correlates Of Early Prosocial Actionmentioning
confidence: 99%